1997
DOI: 10.1074/jbc.272.46.29099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Protein-Glutathione Mixed Disulfide on the Chaperone-like Function of α-Crystallin

Abstract: In an earlier report we showed that incubation of ␣-crystallin with oxidized glutathione results in significant loss of its chaperone-like activity. In the present study, we determined the effect of protein-glutathione mixed disulfides (PSSG), formed at Cys-131 in bovine ␣A-crystallin, and Cys-131 and Cys-142 in human ␣A-crystallin, on the function of ␣-crystallin as a molecular chaperone. After incubation of calf and young human ␣ L -crystallin fractions with oxidized glutathione, levels of PSSG were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Previously, we (7) have proposed that the initiation of oxidative stress-induced cataract may, in part, involve the oxidationinduced PSSG formation in the lens enzymes/proteins, resulting in loss of enzyme activity, such as observed with glyc- eraldehyde-3-dehydrogenase (20) or protein function, as with the chaperone-like function of ␣A-crystallin (54). The extra charge and mass of the -SG group that S-conjugates onto a protein may cause conformational change (55) and/or destabilization of lens crystallin proteins (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we (7) have proposed that the initiation of oxidative stress-induced cataract may, in part, involve the oxidationinduced PSSG formation in the lens enzymes/proteins, resulting in loss of enzyme activity, such as observed with glyc- eraldehyde-3-dehydrogenase (20) or protein function, as with the chaperone-like function of ␣A-crystallin (54). The extra charge and mass of the -SG group that S-conjugates onto a protein may cause conformational change (55) and/or destabilization of lens crystallin proteins (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be especially true for oxidation of tryptophan and tyrosine residues that were not observed in either the test mixture or the cdc2 mixture experiments. Oxidation of methionine residues has been observed when lens crystallins are exposed to hydroxyl radicals, for example in a reaction with Fe ϩ3 and H 2 O 2 (54), and this exposure strongly inhibits chaperone activity (55). Also, it has been suggested that oxidation of tryptophan and tyrosine is initiated by UV radiation (56,57) and can contribute to changes in lens crystallins.…”
Section: Mapping Protein Modification Sites In Human Lens Tissue Withoutmentioning
confidence: 99%
“…Changes in protein levels alone do not imply changes in function as many proteins are known to be regulated by post-translational modifications. Proteins can resolve into multiple spots due to proteolytic processing, multiple isoforms, or changes in charge state resulting from posttranslational modifications, including phosphorylation, deamidation, acetylation, glycation, and glutathionylation (23)(24)(25)(26). It is possible that post-translational modifications may affect in-gel migration of a protein such that a protein classified as repressed may be present elsewhere on the gel or that a putative de novo protein may be found in a new place in the gel.…”
Section: Fig 4 Time-dependent Changes Of the Differentially Expressmentioning
confidence: 99%